Nanoparticle‐Mediated Binning and Profiling of Heterogeneous Circulating Tumor Cell Subpopulations. (5th November 2014) - Mohamadi, Reza M.; Besant, Justin D.; Mepham, Adam; Green, Brenda; Mahmoudian, Laili; Gibbs, Thaddeus; Ivanov, Ivaylo; Malvea, Anahita; Stojcic, Jessica; Allan, Alison L.; Lowes, Lori E.; Sargent, Edward H.; et al.
Abstract: The analysis of circulating tumor cells (CTCs) is an important capability that may lead to new approaches for cancer management. CTC capture devices developed to date isolate a bulk population of CTCs and do not differentiate subpopulations that may have varying phenotypes with different levels of clinical relevance. Here, we present a new device for CTC spatial sorting and profiling that sequesters blood‐borne tumor cells with different phenotypes into discrete spatial bins. Validation data are presented showing that cancer cell lines with varying surface expression generate different binning profiles within the device. Working with patient blood samples, we obtain profiles that elucidate the heterogeneity of CTC populations present in cancer patients and also report on the status of CTCs within the epithelial‐to‐mesenchymal transition (EMT). Abstract : Trennung von Krebszelluntergruppen : Zirkulierende Krebszellen (CTCs) sind inhärent heterogen, und es können Untergruppen mit variierender klinischer Signifikanz existieren. Eine neue Methode unterscheidet den Grad der Bindung magnetischer Nanopartikel an CTC‐Untergruppen mit verschieden starker Markerexpression an der Oberfläche. Dies ermöglicht die Erfassung des Epithel‐zu‐Mesenchym‐Übergangs in den CTCs von Patienten.